Capacity of Vehicular Ad Hoc Networks Based on Multibeam Directional Transmission - Yuhua Wang (Hindawi-Wiley, 2021)
The development of multibeam directional transmission technology used in vehicular ad hoc networks is drawing much more attention in recent years due to its wider coverage ability than omnidirectional transmission. In this paper, we analyse the transport capacity of the vehicular network using different antenna modes in the transmitter and receiver end, respectively. We first construct the cross-layer model comprising the characteristic of the directional antenna model, arbitrary network model, and interference model. Then, based on scaling laws, we calculate the upper and lower bound of the network capacity with and without the directional multibeam transmission technology. In order to reduce the capacity lower bound computation complexity, several topology frameworks are constructed while taking various interferences into account included in the actual project. Finally, we analyse the capacity under changes of different parameters and also evaluate the law of capacity changes to discover how much improvement multibeam transmission technology can bring to the network performance. Analysis shows that compared with DTOR and OTDR mode, DTDR mode can continue to increase network capacity by 2 to 3 times on the basis of the above two modes.